Injertos óseos : nueva alternativa. Fase I. Extracción de proteínas morfogenéticas parcialmente purificadas de hueso bovino (2003)
ABSTRACT: The purpose of this research was to extract from bovine bone and through physical and chemical procedures, Bone Morphogenetic Proteins (BMPs) partially purified, with high-quality osteoinduction characteristics, low antigenicity and high bioavailability. These proteins will be utilized as bone graft material. The procedure was performed through five basic steps: Milling the bovine bone, lipid extraction, demineralization, collagen extraction, obtention of the protein fraction. These steps were verified respectively through the following analysis: The Soxhlet method, Atomic Absorption for Calcium determination, Van Gieson Pycrofucsin Stain., Polyacrilamide Gel-Electrophoresis-Sodium- Duodecyl-Sulphate (PAGE-SDS). BMPs partially purified were obtained through Polyacrilamide Gel-Electrophoresis-Sodium-Duodecyl-Sulphate (PAGE-SDS., with molecular weights between 18 - 120 Kda, mainly bands at 18, 24, 34, 68, 72, 90 and 120 KDa, This material was lyophilized, packed and stored in a vacuum sealed narrow-neck bottle for posterior use.